Cluster-Randomized Trial of a Physician/Pharmacist Collaborative Model to Improve Blood Pressure Control - Carter, Barry L.; Coffey, Christopher S.; Ardery, Gail; Uribe, Liz; Ecklund, Dixie; James, Paul; Egan, Brent; Weg, Mark Vander; Chrischilles, Elizabeth; Vaughn, Thomas (Circulation Cardiovascular quality and outcomes, 2015)
The purpose of this study was to evaluate if a physician/pharmacist collaborative model would be implemented as determined by improved blood pressure (BP) control in primary care medical offices with diverse geographic and patient characteristics and whether long-term BP control could be sustained. Prospective, cluster-randomized trial of 32 primary care offices stratified and randomized to control, 9-month intervention (brief), and 24-month intervention (sustained). We enrolled 625 subjects with uncontrolled hypertension; 54% from racial/ethnic minority groups and 50% with diabetes mellitus or chronic kidney disease. The primary outcome of BP control at 9 months was 43% in intervention offices (n=401) compared with 34% in the control group (n=224; adjusted odds ratio, 1.57 [95% confidence interval, 0.99-2.50]; P=0.059). The adjusted difference in mean systolic/diastolic BP between the intervention and control groups for all subjects at 9 months was -6.1/-2.9 mm Hg (P=0.002 and P=0.005, respectively), and it was -6.4/-2.9 mm Hg (P=0.009 and P=0.044, respectively) in subjects from racial or ethnic minorities. BP control and mean BP were significantly improved in subjects from racial minorities in intervention offices at 18 and 24 months (P=0.048 to P<0.001) compared with the control group. Although the results of the primary outcome (BP control) were negative, the key secondary end point (mean BP) was significantly improved in the intervention group. Thus, the findings for secondary end points suggest that team-based care using clinical pharmacists was implemented in diverse primary care offices and BP was reduced in subjects from racial minority groups. URL: http://www.clinicaltrials.gov. Unique identifier: NCT00935077.